Nanostructured Lipid Carrier to Improve Oral Bioavailability - Harakal, Pooja; Kulkarni, Nilesh; Gore, Suvarna; Khade, Komal; Dhole, Shashikant (Indian Journal of Pharmaceutical Education and Research, 2025)
Oral administration is the best way to administer both traditional and novel drugs because it decreases patient non-compliance and can also relieve the pain and discomfort associated with parenteral preparations. However, despite many benefits of oral formulations, a number of disadvantages significantly impair bioavailability. By helping with site-specific targeting, nanoparticles can stop drugs from breaking down across different physiological barriers. Lipidic systems are regarded as the most evident among all the emerging nano drug carriers. Lipid carriers that are nanostructured are thus created. As these consist of liquid and solid lipid mixes, which make up the safe lipidic colloidal systems. Surfactants are used in system for stabilization. This lipidic formulation offers improved penetration, longer half-life, decreased clearance and greater drug solubility and improves oral bioavailability of various classes of drugs. A type of lipid-based carrier called Nanostructured lipid carrier replaces a certain amount of solid lipid with liquid lipid to get over some of the main drawbacks associated with Solid Lipid Nanoparticles. Research using Nanostructured lipid carriers show that they may be the most advantageous carrier for improving the oral bioavailability of both hydrophilic and lipophilic medications. The article provides a brief overview of the different types, components and fabrication methods of that are employed in formulations, with a primary focus on typical barriers that affect the bioavailability of drugs delivered orally. The article provides advantages with respect to oral bioavailability enhancement are highlighted in this review.
Keywords: Nanostructured Lipid Carrier; Solid Lipid Nanoparticle; Bioavailability; Nanocarriers; Nanoparticles